Pembuktian Hubungan Keperdataan terhadap Penentuan Hak Waris Anak Luar Kawin dalam Sistem Hukum Perdata Indonesia - Gracia Magdalena; I Gede Agus Kurniawan; Ni Putu Sawitri Nandari; Komang Satria Wibawa Putra (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The legal recognition of children born outside marriage in Indonesia remains problematic, particularly regarding the proof of civil relationships with biological fathers and its impact on inheritance rights. Although the Constitutional Court Decision Number 46/PUU-VIII/2010 has expanded such recognition, the absence of clear evidentiary standards continues to create inconsistent judicial interpretations. This study aims to examine the legal construction of proving civil relationships and to analyze its influence on determining inheritance rights within the Indonesian civil law system. The research employs a normative legal method using statutory, conceptual, and case approaches, with data collected through literature study and analyzed qualitatively. The findings show that proof of civil relationship constitutes a fundamental requirement for establishing inheritance rights, however the lack of uniform standards, whether through DNA testing or other legally recognized evidence, leads to varying court decisions and legal uncertainty. This study highlights the need for clearer regulatory guidelines to ensure consistency, legal certainty, and equitable protection of the rights of children born outside marriage.